Phytochemical screening of Alstonia scholaris leaf and bark extracts and their antimicrobial activities - Bagheri, Gholamreza; Ayatollahi, Seyed Abdulmajid; Ramírez-Alarcón, Karina; Fernández, Marcos; Salehi, Bahare; Forman, Katherine; Martorell, Miquel; Heydarian Moghadam, Mohammad; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Alstonia sholaris is an evergreen tree commonly found in South East Asia. In traditional medicine pharmacological activities are attributed to the leaves and bark of this plant. The aim of this study is characterizing the chemicals present in A. sholaris leaves and bark extracts and study their antimicrobial activities. Solvent extractions with Soxhlet apparatus of leaves and bark were obtained using hexane, benzene, isopropanol, methanol, and water. The crude extracts were concentrated and screened for qualitative phytochemical analysis and thin layer chromatography, and the antibacterial, antifungal an antiviral activity of crude extracts were measured by in vitro methods. Isopropanol and methanol extracts showed significant antibacterial activity and it was more pronounced against Gram positive than against Gram negative bacteria. Hexane, benzene, isopropanol and methanol fractions of A. scholaris bark and leaf showed activity against Enterobacter cloacae. Isopropanol extract showed maximum activity against selected human pathogenic fungus. In conclusion, the leaves and bark of A. scholaris are rich in phytochemicals with antimicrobial activities against human pathogens, being the isopropanol fraction the one with the highest antibacterial, antifungal, antiviral and anti-mycobacterial activities.